Union Digital Centres of Trishal Upazila: How Far Entrepreneur’s Financial Competency Is? (Social Science Review, 2022)
Union Digital Centre (UDC), an innovative ingenuity of local government authority, represents a predominant nexus for efficient service delivery in rural areas. It has stimulated Information Technology (IT) and provided other internet based needful public and private services to the millions of underserved people’s doorsteps at their convenience. By adopting this new dimension of entrepreneurship framework in rural economy, citizen friendly bottom-up development could be established. However, to introduce such set-up at periphery level, financial and technological support remains a big challenge. Hence, this study reveals the recent conditions and financial affairs of seven selected UDCs at Trishal Upazila. Both primary and secondary sources of data were collected from the studied area and in-depth interview of 23 individuals was taken in qualitative manner. It is observed that without generous financial supports it is very difficult to retain the financial solvency of the entrepreneurs. Sometimes, these massive financial liabilities, lack of logistic support, inadequate training and unskilled manpower are extensively responsible for gradual losing of interest to execute one stop shops services. Therefore, this study also suggested some necessary policy recommendations to strengthen UDC’s activities by successfully executing the Public Private Entrepreneurship model in studied area.Social Science Review, Vol. 38(1), June 2021 Page 133-156